Accuracy of food preference predictions in couples. (1st February 2019) - Scheibehenne, Benjamin; Mata, Jutta; Richter, David
Abstract: The goal of this study was to identify and empirically test variables that indicate how well partners in relationships know each other's food preferences. Participants (n = 2, 854) lived in the same household and were part of a large, nationally representative panel study in Germany. Each partner independently predicted the other's preferences for several common food items. Results show that predictive accuracy was higher for likes and for extreme and stereotypical preferences as compared to dislikes and for moderate and idiosyncratic preferences. Accuracy was also higher for couples with a high similarity in preferences and with longer relationship duration but was independent of participants' age after controlling for relationship duration. The data also show that relationship duration was accompanied by higher similarity in couples' food preferences. There was a small positive correlation between partner knowledge and both partner similarity and satisfaction with family life, but no correlation between partner knowledge and general life satisfaction. The results reconcile both valence and base-rate accounts of preference prediction accuracy.